Guidelines for Effective Development of Knowledge Management among Personnel at TOT Public Company Limited - Gerdruang, Atiporn (วารสารสันติศึกษาปริทรรศน์ มจร, 2021)
The objectives of this research article were to 1) study the current and desirable conditions for knowledge management among personnel, and 2) propose guidelines for effective development of knowledge management among personnel at TOT Public Company Limited. The study was implemented in the form of mixed-method research; samples comprised 376 TOT personnel and 10 people for a focus group discussion. Using analysis by statistical packages. The results of the study were as follows: 1) The study results of the current and desirable conditions of personnel’s effective knowledge management under TOT in all aspects were at a high level; 2) Guidelines for effective knowledge management of personnel under the TOT consisted of 7 areas. These areas included 1) knowledge definition with very vital guidelines, 2) creating and seeking knowledge, 3) organizing knowledge systematically, 4) processing and filtering knowledge, 5) accessing knowledge, 6) sharing and exchanging knowledge, and 7) learning and applying knowledge. These elements will cause a change in the management of people with tacit knowledge, transferring as much knowledge as possible to create the most knowledge and benefit to the organization.